Dark-field X-ray imaging for the assessment of osteoporosis in human lumbar spine specimens - Gassert, Florian T.; Urban, Theresa; Kufner, Alexander; Frank, Manuela; Feuerriegel, Georg C.; Baum, Thomas; Makowski, Marcus R.; Braun, Christian; Pfeiffer, Daniela; Schwaiger, Benedikt J.; Pfeiffer, Franz; Gersing, Alexandra S. (Frontiers in Physiology, 2023)
Background: Dark-field imaging is a novel imaging modality that allows for the assessment of material interfaces by exploiting the wave character of x-ray. While it has been extensively studied in chest imaging, only little is known about the modality for imaging other tissues. Therefore, the purpose of this study was to evaluate whether a clinical X-ray dark-field scanner prototype allows for the assessment of osteoporosis.In this prospective study we examined human cadaveric lumbar spine specimens (vertebral segments L2 to L4). We used a clinical prototype for dark-field radiography that yields both attenuation and dark-field images. All specimens were scanned in lateral orientation in vertical and horizontal position. All specimens were additionally imaged with CT as reference. Bone mineral density (BMD) values were derived from asynchronously calibrated quantitative CT measurements. Correlations between attenuation signal, dark-field signal and BMD were assessed using Spearman's rank correlation coefficients. The capability of the dark-field signal for the detection of osteoporosis/osteopenia was evaluated with receiver operating characteristics (ROC) curve analysis.Results: A total of 58 vertebrae from 20 human cadaveric spine specimens (mean age, 73 years ± 13 [standard deviation]; 11 women) were studied. The dark-field signal was positively correlated with the BMD, both in vertical (r = 0.56, P < .001) and horizontal position (r = 0.43, P < .001). Also, the dark-field signal ratio was positively correlated with BMD (r = 0.30, P = .02). No correlation was found between the signal ratio of attenuation signal and BMD (r = 0.14, P = .29). For the differentiation between specimens with and without osteoporosis/osteopenia, the area under the ROC curve (AUC) was 0.80 for the dark-field signal in vertical position.Conclusions: Dark-field imaging allows for the differentiation between spine specimens with and without osteoporosis/osteopenia and may therefore be a potential biomarker for bone stability.